The approaches for localized surface plasmon resonance wavelength position tuning. Short review - Demydov, P.V.; Lopatynskyi, A.M.; Hudzenko, І.І.; Chegel, V.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
A unique feature of nanoparticles made from highly conductive materials (plasmonic nanoparticles) is that their localized surface plasmon resonance (LSPR) wavelength position can be tuned by changing the shape, size, composition, and environment in accordance with the purpose of the application. In this paper, the main mechanisms of LSPR tuning that are available at the present time are reviewed. In particular, a widely used method for tuning the LSPR wavelength position is based on selecting the type of plasmonic nanoparticle material, such as gold, silver, copper, aluminum, and gold-silver alloy. The examples of changing the resonance absorption position by using nanoparticles with different shapes and dimensions have also been аlso demonstrated. Furthermore, works with less-used LSPR tuning methods, such as controlled regulation of the distance between nanoparticles in one and two dimensions, have been considered. The number of works is given, where the LSPR wavelength position can also be controlled by changing the environment in the vicinity of the plasmonic nanoparticle: the substrate thickness, the thickness and dielectric parameters of the layer on the surface of the nanoparticle. Examples of active influence on the change in the wave position of LSPR by applying an electric potential and regulating plasma modes have also been discussed. Унікальною особливістю наночастинок з високопровідних матеріалів (плазмонні наночастинки) є той факт, що їх хвильову позицію локалізованого поверхневого плазмонного резонансу (ЛППР) можна регулювати, змінюючи форму, розмір, склад і оточуюче середовище відповідно до цілей застосування. У даному огляді наведено приклади основних механізмів регуляції ЛППР, доступних на даний час. Серед найбільш вживаних методів регуляції хвильової позиції ЛППР – використання різного типу матеріалів наночастинок – золота, срібла, міді, алюмінію та сплаву золото-срібло. Також наведено приклади зміни резонансної позиції поглинання шляхом використання наночастинок з різною формою та розмірністю. Розглянуто використання менш вживаних методів регуляції ЛППР, таких як контрольована регуляція відстані між частинками в одному і двох вимірах. Описано роботи, де хвильову позицію ЛППР регулюють за рахунок зміни оточуючого середовища: товщини підкладки, товщини та діелектричних параметрів шару на поверхні наночастинки. Також розглянуто приклади активного впливу на зміну хвильової позиції ЛППР шляхом прикладання електричного потенціалу та регуляції плазмових мод.